Coprescription Trends in Western Medicine, Chinese Herbal Medicine and Dental Medicine among Older Adults in Taiwan from 1997 to 2013. (December 2021) - Huang, Chia-Yu; Wu, Mei-Yao; Chang, Chia-Ling; Liao, Yuan-Ching; Chen, Ying-Yu; Lin, Wu-Chou; Yen, Hung-Rong
Abstract: Background: Coprescription is a potential medical problem for older adults that could induce polypharmacy and subsequent complications. In Taiwan, Chinese herbal medicine (CHM) is popular among the older adults. Investigating the coprescription trends in Western medicine, CHM and dental medicine is important to avoid possible polypharmacy. Methods: We analyzed data from the Longitudinal Health Insurance Database 2000 (LHID 2000) in Taiwan. Patients ≥ 60 years old who received coprescription of Western medicine, CHM and drugs for dental care from 1997 to 2013 were included. The odds ratio (OR) and 95% confidence interval (95% CI) were estimated by a logistic regression model for evaluating the correlation between baseline characteristics and coprescription. Results: A total of 266, 034 patients were included for the analysis. Most patients receiving coprescriptions lived in the northern Taiwan and with a monthly income lower than 20, 000 new Taiwan dollars. The trends in older adults using Western medicine alone or CHM alone decreased over time, but the cohort using dental medicine alone had the opposite result. Decreased trends in coprescription with age were noted. The trends in the proportion of coprescription and the number of days of coprescription increased with the calendar year. Increased trends in the proportion of patients with coprescription were also found, except for the cohort of patients who used both Western medicine and CHM. Patients who were female, and aged 70–79 years were prone to receive coprescription. Conclusions: Coprescription in older patients is not uncommon in Taiwan. Healthcare providers and policymakers should be aware of the complex coprescription pattern in the older adults. Highlights: Coprescription is a potential medical problem for older adults and not uncommon in Taiwan. Patients who were female and aged 70–79 years were prone to receive coprescription. Healthcare providers and policymakers should be aware of the complex coprescription pattern in the older adults.